Multiplexed detection of respiratory viral pathogens by isothermal amplification on an autonomously loaded chip at the point-of-care - Berzina, Beatrise; Gupta, Krishna; Suliman, Rayan; Mirtschink, Peter; Dalpke, Alexander; Werner, Carsten; Krieg, Elisha; Renner, Lars David (Lab on a chip, 2025)
Recent viral outbreaks have shown the need for reliable diagnostic platforms to rapidly detect various viral and bacterial pathogens at the point-of-care. Over the last decade, isothermal nucleic acid amplification methods have emerged as an appealing alternative to standardized polymerase chain reaction (PCR) tests due to their high sensitivity, selectivity, low cost, and simple assay setup. Virtually all nucleic acid testing platforms require a labor-intensive sample preparation step, limiting the scalability and usability of recent alternatives. This article describes multiplexed isothermal detection of respiratory viruses on a valve-free, autonomously loading microfluidic platform - VirChip. We demonstrate that an optimized loop-mediated isothermal amplification (LAMP) enables the simultaneous detection of SARS-CoV-2, influenza A, influenza B, and RSV (A/B) with a limit of detection of 100 RNA copies per reaction. The platform is highly selective, as no cross-reactivity amongst the targeted pathogens was observed in patient samples. Furthermore, crude nasal swab samples can be directly applied to the chip, eliminating the requirement for expensive and laborious RNA isolation and sample workup. VirChip facilitates rapid, inexpensive, and multiplexed detection, allowing pathogen screening by primary care providers not only in hospitals but also in resource-limited areas.
Veröffentlicht: 01. Oktober 2025
Gesehen am 05.12.2025